Regioselective Synthesis of 2,4- and 2,5-Disubstituted 1,3-Thiazoles from 2-Oxo-2-(amino)ethanedithioates via Base-Catalyzed Cyclization - Singh, Krishna Ravi; Santhosh, Chikkappaiahnayaka; Sheela, Kalleshappa; Sadashiva, Maralinganadoddi P. (Synthesis, 2023)
Facile and efficient methods are reported for the synthesis of 2,4- and 2,5-disubstituted-1,3-thiazoles by the cyclization of 2-oxo-2-(amino)ethanedithioates with TosMIC and α-haloketones in high yields. Key structures were confirmed based on X-ray crystallographic studies. In addition, investigation of ground state geometry, electronic and molecular structural properties, FMOs, global reactivity descriptors, MEP and NCI analyses were predicted to access the information related to the stability, reactivity, and strength of the interactions present in the molecules by quantum chemical calculations. Further, the potency of derivatives was tested against the SARS-Cov2 receptor (PDB ID: 7mc6) via molecular docking approach with binding scores of –6.0 to –8.4 kcal/mol.
Keywords: thiazole; TosMIC; α-haloketones; X-ray crystallographic studies; DFT Studies; molecular docking